2018
DOI: 10.1093/icesjms/fsy016
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits estimated from weight-related isotope variations of mesopelagic fish larvae in the Kuroshio waters of the northeastern East China Sea

Abstract: Bulk carbon and nitrogen stable isotope (SI) ratios (δ13C and δ15N) were analysed to investigate the feeding habits of six taxa of mesopelagic fish larvae inhabiting the Kuroshio waters of the northeastern East China Sea. Large variation in tissue SI during early larval periods suggested maternal effects from parent fishes, and non-selective feeding on a variety of plankton species due to poor swimming ability. The similarity between SI ratios measured in larval tissues and those estimated for eggs of an “inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…We know that A. rochei are non-migratory, and are income breeders in the Mediterranean (Alemany et al 2010); it is reasonable assume that this species also exerts an income breeding strategy in the GOM. Further comparative research on reproductive energetics is clearly necessary but, in accordance with Tanaka et al (2016) and Mei et al (2018), our results suggest that SIA of larvae could be a potential tool to infer information on the type of breeding strategy.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We know that A. rochei are non-migratory, and are income breeders in the Mediterranean (Alemany et al 2010); it is reasonable assume that this species also exerts an income breeding strategy in the GOM. Further comparative research on reproductive energetics is clearly necessary but, in accordance with Tanaka et al (2016) and Mei et al (2018), our results suggest that SIA of larvae could be a potential tool to infer information on the type of breeding strategy.…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, based on diet-switching feeding experiments, Tanaka et al (2016) successfully demonstrated that Japanese anchovy Engraulis japonicus were income breeders because the δ 15 N bulk and δ 13 C bulk ratios in eggs closely followed the isotope ratios of the food of adult fish. Under this paradigm, Mei et al (2018) applied SIA on the smallest larvae of 6 mesopelagic species, which revealed the dominant spawning strategy (breeder type). Taking into account breeding type (income or capital breeder) of fishes may allow interpretation of differences or similarities between the SIA bulk ratios measured in field-captured fish larvae (Tanaka et al 2016, Mei et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated DR showed that D. fulgens adults continue to eat food actively during the spawning season, suggesting the characteristics of income breeders. Mei et al (2019) also suggested an income breeder strategy in D. fulgens in the Kuroshio waters, based on the similarity between carbon and nitrogen stable isotope ratios measured in larval tissues and those estimated for eggs. Diaphus fulgens can be considered to spawn using energy acquired during the spawning season, allocating energy directly to reproduction.…”
Section: Diel Feeding Periodicity and Daily Rationmentioning
confidence: 99%